2001
DOI: 10.1097/00008469-200102000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer in relation to anthropometry, blood pressure, blood lipids and glucose metabolism: a prospective study within the Malmö Preventive Project

Abstract: Insulin resistance may be a risk factor for breast cancer, possibly through increased levels of oestrogens or insulin-like growth factor I. Insulin resistance has been associated with obesity, hypertension, dyslipidaemia and impaired glucose tolerance. We studied the relation of these factors to breast cancer risk in a prospective cohort study of 9738 women. Menopausal status was defined a priori, and 112 cases of invasive breast carcinoma occurred in women who were premenopausal at baseline and 157 cases in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 32 publications
3
82
3
Order By: Relevance
“…Also, additional research into the pathways involved in the interrelationships between hypertension, antihypertensive medication use and breast cancer is warranted. What is known about this topic K Hypertension has been linked to some cancer types including renal and endometrial cancers 7-11 K Studies on hypertension and breast cancer have produced mixed results 4,6,9,[12][13][14] What this study adds K This study supports a positive association between treated hypertension and breast cancer among women aged 50-75 years after adjusting for age, BMI, diabetes, smoking, alcohol use, menopausal status, family history of breast or ovarian cancer, age at first full-term pregnancy and education K The association between hypertension and breast cancer was observed only among women with a BMI X25 kg/m 2 K A dose-response association was observed between duration of diuretic use and breast cancer risk Abbreviation: BMI, body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, additional research into the pathways involved in the interrelationships between hypertension, antihypertensive medication use and breast cancer is warranted. What is known about this topic K Hypertension has been linked to some cancer types including renal and endometrial cancers 7-11 K Studies on hypertension and breast cancer have produced mixed results 4,6,9,[12][13][14] What this study adds K This study supports a positive association between treated hypertension and breast cancer among women aged 50-75 years after adjusting for age, BMI, diabetes, smoking, alcohol use, menopausal status, family history of breast or ovarian cancer, age at first full-term pregnancy and education K The association between hypertension and breast cancer was observed only among women with a BMI X25 kg/m 2 K A dose-response association was observed between duration of diuretic use and breast cancer risk Abbreviation: BMI, body mass index.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a growing body of literature on the relation between obesity and post-menopausal breast cancer risk, the pathways responsible are still under investigation. 3 It has been hypothesized that hypertension and breast cancer may be associated owing to shared risk factors such as high body mass index (BMI) or metabolic syndrome, 4 or common pathophysiologic pathways including those involved in insulin resistance, 5 and hormone synthesis and metabolism. 6 Several studies have examined associations between hypertension and cancer risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were independent of adiposity and body fat distribution. However, in the Malmo Preventive Project, when looking at fasting blood glucose and blood glucose levels after an oral glucose challenge no relationship was found with breast cancer in peri-and postmenopausal women (Manjer et al, 2001).…”
Section: Breast Cancermentioning
confidence: 96%
“…Previous small studies have proclaimed a link with hypertension and breast cancer, [14][15][16][17] whereas others failed to find any association. [18][19][20] A meta-analysis of five case-control studies by Grossman et al 21 reported a nonsignificant increase in risk (adjusted OR 1.14; 95% CI 0.9-1.4). Similarly, prospective large randomized clinical trials such as Syst-Eur, Antihypertensive and Lipid-Lowering treatment to prevent Heart Attack Trial (ALLHAT), 22 Systolic Hypertension in the Elderly Program (SHEP) 4 and STOP-2 did not find any increased cancer risk with antihypertensive treatment and many consider this to be the definitive answer to the antihypertensives cancer debate.…”
mentioning
confidence: 99%